Treatment of active ankylosing spondylitis with abatacept: an open-label, 24-week pilot study. Issue 6 (17th March 2011) - Song, I-H; Heldmann, F; Rudwaleit, M; Haibel, H; Weiß, A; Braun, J; Sieper, J
Abstract : Objective: To prospectively explore the short-term efficacy and safety of abatacept in patients with ankylosing spondylitis (AS). Methods: In this prospective open-label pilot study, abatacept (10 mg/kg) was administered intravenously on days 1, 15, 29 and every 28 days thereafter up to week 24 in 15 tumour necrosis factor α (TNFα)-inhibitor naive patients (group 1) and 15 patients with inadequate response to TNFα inhibitors (group 2) with active AS. The primary end point was the proportion of patients with 40% improvement according to the Assessment of SpondyloArthritis international Society criteria (ASAS40) in both groups at week 24. Results: At week 24, ASAS40 was reached by 13% of group 1 and 0% of group 2; 20% improvement (ASAS20) was reached by 27% and 20%, respectively. There was no significant change of Bath Ankylosing Spondylitis Disease Activity Index score, patient global assessment or C reactive protein. Overall, abatacept was well tolerated. Conclusions: In this pilot open-label AS study a major response was not observed.